Design and analysis of a new flexure-based XY stage. (October 2017) - Yang, Yiling; Wei, Yanding; Lou, Junqiang; Xie, Fengran
This article presents the design, modeling, and experimental testing of a novel piezo-driven XY stage with parallel, decoupled, and compact kinematic structure. The structural design of the stage is based on a hybrid compliant mechanism employing the right-circular double-rocker mechanism and the leaf-type parallelogram mechanism. The proposed XY stage is capable of producing a large workspace range, an excellent decoupled motion, and a suitable resonant frequency. By means of the pseudorigid-body-model method, the theoretical models of the XY stage are derived. Using the finite element analysis simulations, the optimal structural parameters are acquired, and the theoretical models are analyzed and validated. A prototype of the proposed stage was finally manufactured, and several experimental investigations were performed to validate its performances. The experimental results show that the XY stage has a large amplification ratio of 7.48 and a large workspace range of 150.3 µm × 147.9 µm. In addition, the parasitic motion along the y -axis ( x -axis) accounts for 0.94% (0.74%) of the x -axis ( y -axis) motion, which indicates that the stage possesses excellent decoupling characteristics.